The Influence of Cyclical Ketogenic Reduction Diet vs. Nutritionally Balanced Reduction Diet on Body Composition, Strength, and Endurance Performance in Healthy Young Males: A Randomized Controlled Trial - Kysel, Pavel; Haluzíková, Denisa; Doležalová, Radka Petráková; Laňková, Ivana; Lacinová, Zdeňka; Kasperová, Barbora Judita; Trnovská, Jaroslava; Hrádková, Viktorie; Mráz, Miloš; Vilikus, Zdeněk; Haluzík, Martin (Nutrients, 2020)
(1) Background: The influence of ketogenic diet on physical fitness remains controversial. We performed a randomized controlled trial to compare the effect of cyclical ketogenic reduction diet (CKD) vs. nutritionally balanced reduction diet (RD) on body composition, muscle strength, and endurance performance. (2) Methods: 25 healthy young males undergoing regular resistance training combined with aerobic training were randomized to CKD (n = 13) or RD (n = 12). Body composition, muscle strength and spiroergometric parameters were measured at baseline and after eight weeks of intervention. (3) Results: Both CKD and RD decreased body weight, body fat, and BMI. Lean body mass and body water decreased in CKD and did not significantly change in RD group. Muscle strength parameters were not affected in CKD while in RD group lat pull-down and leg press values increased. Similarly, endurance performance was not changed in CKD group while in RD group peak workload and peak oxygen uptake increased. (4) Conclusions: Our data show that in healthy young males undergoing resistance and aerobic training comparable weight reduction were achieved by CKD and RD. In RD group; improved muscle strength and endurance performance was noted relative to neutral effect of CKD that also slightly reduced lean body mass.
Keywords: svalová síla; Resistance Training; ketogenic diet; Humans; redukční dieta; složení těla; Diet, Reducing; Physical Endurance; mladý dospělý; dospělí; Diet, Ketogenic; lidé; endurance; odporový trénink; body composition; fyzická vytrvalost; Muscle Strength; Adult; Male; training; Adolescent; strength parameters; Body Composition; Young Adult; Exercise; ketogenní dieta; mužské pohlaví; cvičení; mladiství